Frequency of Participation in a Return-to-Work Program Predicts Successful Work Restoration but Not Maintenance - Hoaki, Yuriko; Terao, Takeshi (Frontiers in Psychiatry, 2021)
Several predictors for work restoration and maintenance of restoration have been examined among employees with mood and/or anxiety disorders, but whether frequency of participation in a return-to-work (RTW) program can predict successful work restoration and maintenance remains unclear. In the present study, we attempted to investigate the hypothesis that the frequency of RTW program participation can predict successful work restoration and maintenance. Among seventy-seven patients attending an RTW program, the frequency of participation was positively associated with work restoration but not with maintenance. The result was in partial agreement (restoration) and partial disagreement (maintenance of restoration) with our hypothesis. Thus, the present study suggests that the frequency of participation in an RTW program can predict successful work restoration but not maintenance.